If 1, log x (base y), log y (base z), -15 log z (base x)
are in AP, then
a) z^3 = x
b) x = y^-1
c) z^-3 = y
d) all of these
Follow Math Help Forum on Facebook and Google+
Let the common difference be d. Then the progression is 1, d+1, 2d+1, and 3d+1, so
Combining the first two gives , and equating exponents gives (3d+1)(2d+1)(d+1)=-15, with the only solution d=-2.
Hello, yshridhar! Lovely work, Hollywood! . .
Hollywood had: .
Then we have: . . . . . .
Thanks alot Hollywood for such a simple solution. I am banging with logarithms formulae for this sum.
View Tag Cloud